2006
DOI: 10.1007/s00436-006-0405-7
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole therapy for eosinophilic meningitis caused by Angiostrongylus cantonensis

Abstract: Eosinophilic meningitis in humans is commonly caused by the nematode Angiostrongylus cantonensis. A severe headache is the most common presenting symptom. A prospective, randomized, double-blind, placebo, controlled study was conducted to determine if albendazole was efficacious in relieving such headaches. Seventy-one patients (36 and 35 in the treatment and control groups) were enrolled in the study. Five patients (two and three in the treatment and control groups) were excluded from the study because of bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 10 publications
0
40
0
1
Order By: Relevance
“…Prednisone significantly reduced the proportion of patients with persistent headaches after completion of the treatment (9.1% compared to 45.5% in the placebo group; P ϭ 0.0004), the mean duration of headache (5 days compared to 13 days; P ϭ 0.0), and the number of repeated lumbar punctures for pain relief (7 compared to 22; P ϭ 0.02) (52). The 2-week course of albendazole reduced the proportion of patients with persistent headaches from 20.6% to 40.6% in the placebo group (P ϭ 0.08), and the mean duration of headache was reduced from 8.9 to 16.2 days (P ϭ 0.05) (138). While a 2-week course of prednisolone (60 mg/day) may be recommended in meningitis caused by A. cantonensis, the value of albendazole or mebendazole therapy in conjunction with corticosteroids is not yet fully established, since most of the data come from uncontrolled studies or clinical reports of a few patients (51,127,230,281,293).…”
Section: Treatmentmentioning
confidence: 99%
“…Prednisone significantly reduced the proportion of patients with persistent headaches after completion of the treatment (9.1% compared to 45.5% in the placebo group; P ϭ 0.0004), the mean duration of headache (5 days compared to 13 days; P ϭ 0.0), and the number of repeated lumbar punctures for pain relief (7 compared to 22; P ϭ 0.02) (52). The 2-week course of albendazole reduced the proportion of patients with persistent headaches from 20.6% to 40.6% in the placebo group (P ϭ 0.08), and the mean duration of headache was reduced from 8.9 to 16.2 days (P ϭ 0.05) (138). While a 2-week course of prednisolone (60 mg/day) may be recommended in meningitis caused by A. cantonensis, the value of albendazole or mebendazole therapy in conjunction with corticosteroids is not yet fully established, since most of the data come from uncontrolled studies or clinical reports of a few patients (51,127,230,281,293).…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized controlled trial of 71 patients with eosinophilic meningitis showed a statistically significant decrease in headache duration from 16.2 to 8.9 days with albendazole treatment compared with placebo. 10 Still, other studies report exacerbations of neurologic symptoms when anti-helminthic drugs are used alone for treatment, likely due to an inflammatory response to the dying parasite. 11 Further studies to define the optimal treatment strategy are needed.…”
Section: Denouementmentioning
confidence: 99%
“…Meningitic angiostrongyliasis can be diagnosed using clinical criteria (Chotmongkol et al 2000, Jitpimolmard et al 2007, ramirez-Avila et al 2009), including a percentage of cerebrospinal fluid eosinophils that is greater than 10% and a history of eating raw fresh-water snails or other transmission hosts. Our serologic test is very specific for meningitic angiostrongyliasis (99% specificity), but the sensitivity is 55.6%.…”
Section: Abstract: Eosinophilia -Diagnosis -Meningitis -Angiostrongymentioning
confidence: 99%
“…Blood eosinophilia has been observed in 30-80% of patients with angiostrongyliasis (Chotmongkol et al 2000, Jitpimolmard et al 2007. The aim of the present study was to evaluate the utility of blood eosinophils as a diagnostic tool for meningitic angiostrongyliasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation